Single-Balloon Enteroscopy—Guided ERCP in Surgically Altered Anatomy Is Safe and Highly Effective: Results from a Prospective Study - Pal, Partha; Kulkarni, Sujay Ashok; Chaudhari, Hrushikesh; Ramchandani, Mohan; Reddy, P. Manohar; Shrimal, Pankaj Kumar; Reddy, D. Nageshwar; Tandan, Manu (Journal of Digestive Endoscopy, 2019)
Objectives Single-balloon enteroscopy (SBE)—assisted endoscopic retrograde cholangiopancreatography (ERCP) has been shown to be cost effective and less technically demanding than other modes of device-assisted enteroscopy. We aimed to evaluate the safety and efficacy of SBE-ERCP in surgically altered anatomy.Methods This was a prospective cohort study in a high-volume tertiary care gastroenterology center. Patients with surgically altered anatomy requiring pancreaticobiliary interventions, who failed ERCP with a colonoscope/duodenoscope, underwent SBE-ERCP. Diagnostic and therapeutic success, procedure time, and adverse events were evaluated prospectively with short-term follow-up.Results Twenty-eight patients with surgically altered anatomy (19 males, aged 15–66 years) underwent total 40 SBE-ERCP (23 Roux-en-Y, 17 Billroth II anatomy) procedures. The ERCP diagnosis were hepaticojejunostomy (HJ) stricture (N = 10), HJ stricture and stone (N = 7), common bile duct (CBD) stricture (N = 6), CBD stone (N = 1), pancreaticojejunostomy (PJ) stricture (N = 1), and pancreatic duct (PD) stricture (N = 1). Diagnostic success was achieved in 91.3% (21/23) patients with Roux-en-Y anatomy and 100% (17/17) with Billroth II anatomy. Therapeutic success was achieved in 86.95% (20/23) and 94.1% (16/17) patients with Roux-en-Y and Billroth II anatomy, respectively. In patients with intact papilla (N = 8), diagnostic and therapeutic success were achieved in 100% (8/8) and 75% (6/8) cases, respectively. The mean procedure time for Roux-en-Y and Billroth II anatomy were 64.95 minutes (range 30–110 min) and 38.31 minutes (range 25–60 min), respectively. Immediate complications occurred in 7.5% (3/40) procedures (2 requiring laparotomy, 1 treated endoscopically) in the form of perforation. Among delayed complications, 5 patients had cholangitis and 1 had recurrent cholestasis, which were successfully treated with stent exchange. No other complications occurred over median follow-up of 110 days (30–390 d).Conclusion SBE-ERCP in surgically altered anatomy requiring pancreatic–biliary intervention appears safe and highly effective with current long ERCP accessories. Further improvement in SBE-ERCP technique and accessories has the potential to make it a promising avenue in surgically altered anatomy.
Keywords: single-balloon enteroscopy; endoscopic retrograde cholangiopancreatography; surgically altered anatomy